2011
DOI: 10.3109/09553002.2011.572112
|View full text |Cite
|
Sign up to set email alerts
|

hTERT regulation by NF-κB and c-myc in irradiated HER2-positive breast cancer cells

Abstract: The present study suggests that following irradiation, HER2 receptor activates hTERT/telomerase, increasing the breast cancer cells' survival potential, through sequential induction of transcription factors NF-κΒ and c-myc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…However, some of these effects seem to rely on nontelomeric activities of TERT. Furthermore, a similar mechanism has also been reported in breast cancer cell lines (Papanikolaou et al, 2011). Finally, telomerase can also regulate NF-κB activity through direct interaction with p65 to promote transcription of a NF-κB target gene subset, demonstrating the existence of a feed-forward mechanism between NF-κB and telomerase at least in cancer cells .…”
Section: Nf-κb and Telomeressupporting
confidence: 66%
“…However, some of these effects seem to rely on nontelomeric activities of TERT. Furthermore, a similar mechanism has also been reported in breast cancer cell lines (Papanikolaou et al, 2011). Finally, telomerase can also regulate NF-κB activity through direct interaction with p65 to promote transcription of a NF-κB target gene subset, demonstrating the existence of a feed-forward mechanism between NF-κB and telomerase at least in cancer cells .…”
Section: Nf-κb and Telomeressupporting
confidence: 66%
“…They showed a relationship between the HER2 receptor and hTERT involving NF-B signalling for increased radio-resistance in breast cancer [80]. The authors demonstrated that the HER2 receptor could be a functional transcriptional regulator of hTERT expression through NF-B and the myc/mad/max network in breast cancer cells after irradiation.…”
Section: Interaction Of Telomerase and Nf-b For In-flammation And Canmentioning
confidence: 98%
“…Sequential induction of Nuclear Factor-kappa B (NF-κB) and c-Myc has been suggested to aid human epidermal growth factor receptor 2 (HER2) in the activation of hTERT following irradiation (Papanikolaou et al, 2011). It was determined that the knockdown of HER2 led to the down-regulation of NF-κB and c-Myc-mediated hTERT and telomerase activity in human breast cancer cells (Papanikolaou et al, 2011). Deng et al (2007) identified the activating enhancer binding protein-2β (AP-2β) as a unique transcriptional activator of hTERT in human lung cancer cells.…”
Section: The Htert Promoter and Associated Transcription Factorsmentioning
confidence: 99%